The Role of Personality Traits in Predicting the Spiritual Intelligence of Senior High School Students in Bostanabad - Abbas Asghari Sharabiani; Nesa Kazemi; Seyyed Valiollah Mousavi (Shahid Beheshti University of Medical Sciences, 2019)
For downloading the full-text of this article please click here. Background and Objective: Nowadays, scientists of different fields pay a special attention to spirituality as a transcendent aspect of every person's life. Several studies have shown that personality traits and spiritual intelligence are two structures that affect each other. The aim of this study was to predict the spiritual intelligence of senior high school students in Bostanabad based on personality traits. Method: This descriptive study adopted a cross-sectional design. The statistical population of the study consisted of all male senior high school students in Bostanabad in the 1395-96 educational year. 180 students were selected by multi-stage cluster random sampling. King's Spiritual Intelligence Self-Report Inventory and NEO Personality Inventory were used for collect data. The gathered data were analyzed using descriptive (mean and standard deviation) and inferential statistics (correlation coefficient and multiple regressions). All ethical issues were observed in this study and the researchers declared no conflict of interests. Results: The results of Pearson correlation coefficients showed that there were significant correlations between spiritual intelligence and the four factors of extroversion, openness to experience, pleasure and conscientiousness. On the other hand, neuroticism had a negative significant correlation with spiritual intelligence (p<0.001). Also, the results of regression analysis showed that conscientiousness, openness to experience, and pleasure could significantly predict students' spiritual intelligence (P<0.01). Conclusion: The results of the research show a close relationship between personality and spiritual intelligence. Accordingly, education officials, psychologists and counselors can use these results to enhance students' personality and their spiritual excellence. For downloading the full-text of this article please click here. Please cite this article as: Asghari SharabianiA, Kazemi A, MousaviSV. The Role of Personality Traits in Predicting the Spiritual Intelligence of Senior High School Students in Bostanabad. J Res Relig Health. 2019; 4(5): 67- 76.